Meningkatkan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran Means Ends Analysis (MEA) di kelas VI SD - Andi Oktaviani; Fatimah Kadir; Muhammad Ilham (Diniyah: Jurnal Pendidikan Dasar, 2022)
This research was conducted because the results of students' mathematics learning were still low due to the inappropriate application of learning models. The purpose of this research is to examine the improvement of student learning outcomes by applying the Means Ends Analysis (MEA) model. This research is a class action research, conducted at SDN Satap 2 Konawe Selatan in 2 cycles. The subject of this research is class VI students in the 2021/2022 academic year, with a total of 22 students. The instruments used are teacher and student observation sheets, learning achievement tests and documentation. The research procedure starts from planning, implementing actions, observing, evaluating and reflecting. The research findings show that students' mathematics learning outcomes have increased significantly after the MEA learning model was implemented. Student completeness in pre-cycle reached 18.18% with an average score of 39.22. After the first cycle of action, students' learning completeness reached 50% with an average score of 53.63 and continued to increase in cycle II with a percentage of student learning completeness of 81.81% and an average score of 75.45.Keywords: Mathematics learning outcome, MEA, elementary school